FEBUXOSTAT MODULATES OXIDATIVE AND APOPTOTIC PATHWAYS IN ACUTE DOXORUBICIN‑INDUCED CARDIOTOXICITY: AN EXPERIMENTAL ANIMAL MODEL STUDY - AL‑KURAISHY, HAYDER M; AL‑GAREEB, ALI I; HANY AKEEL NAJI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: Doxorubicin is one of the most important and powerful anticancer drugs, the most pronounced limitation for its use is toxicity on normal cells. Mechanism of doxorubicin-induced cardiotoxicity (DIC) is multifactorial and complex, including direct DNA damage, formation of free radicals, interference with DNA repair, and activation of immune reactions. Febuxostat is a non-purine-selective xanthine oxidase inhibitor decrease the production of uric acid. The aim of the present study was to evaluate the influence of febuxostat on doxorubicin-induced acute cardiotoxicity in rats regarding oxidative stress and antiapoptotic effects. Methods: A total of 30 Sprague Dawley male rats were used which subdivided into three groups: Group I (negative control group) received normal saline for 10 days, Group II (positive control group) received normal saline plus single dose of doxorubicin (15 mg/kg, IP), and Group III (treated group) received febuxostat (10 mg/kg, po), for 10 successive days plus single dose of doxorubicin (15 mg/kg, I.P.). Serum brain natriuretic peptide (BNP), cardiac troponin I (cTn-I), caspase-3, glutathione peroxidase (GSH-Px), lipid peroxidase (LPO), malondialdehyde (MDA), and tumor necrosis factor alpha were estimated by ELISA kit method. Results: Febuxostat administration before doxorubicin led to significant decrease on cardiac troponin, caspase-3, and elevation in GSH-Px levels significantly p<0.05. While the effects of febuxostat on BNP, LPO, MDA, tumor necrosis-alpha were insignificant p>0.05 compare to doxorubicin. Conclusion: Febuxostat attenuates DIC through modulation of antioxidant, anti-inflammatory, and antiapoptotic biomarkers.